The Study of Physic Chemical Properties and Preference Level of Instant Porridge Made of Pumpkin and Brown Rice - Agus Slamet; Bayu Kanetro; Agus Setiyoko (Food, Agriculture and Natural Resources - NETWORKS, 2021)
Pumpkin (Cucurbita moschata D.) is an annual plant from the Cucurbitaceae family. The availability of pumpkins in Indonesia is relatively high. Pumpkin production in Indonesia reaches an average of 21 tons per hectare. Pumpkin has high carotenoid content reaching 160 mg/100 g. Pumpkin comes from the family Cucurbitaceae and the genus Cucurbita. The cultivar (Cucurbita moschata D.), which is common for human consumption, is referred to as pumpkin. Rice is a food ingredient as a source of energy for humans. In addition, rice is also a source of protein, vitamins, and minerals beneficial for human health. Based on the color of rice, there are several types of rice in Indonesia, such as white rice, black rice, glutinous rice, and brown rice. Brown rice is generally consumed without going through the grinding process, but it is only ground into broken rice and the husk is still attached to the endosperm. Both of these materials have the potential to be processed into instant porridge. In order to produce an instant porridge that has physicochemical properties and meets consumers’ preferences, it is necessary to optimize different mixtures and ensure the right drying temperature.The research investigated different mixtures of pumpkin and brown rice at different ratios of 25:75, 50:50, and 75:25. Variations of drying temperatures include 150°C, 160°C, and 170°C. The resulting instant porridge was tested for physical properties; color, water absorption capacity, oil absorption capacity, bulk density, and extraction yield. The instant porridge preference test was based on color, aroma, taste, consistency, and overall preference. The instant porridge mostly preferred by the panelists was analyzed for identifying the chemical properties. The data obtained were tested in a completely randomized design. When the analysis marked a significant difference, the Duncan Multiple Range Test was run at a significance level of 5%. The results showed that instant porridge based on physical, chemical, and preference characteristics was influenced by different mixtures of brown rice and different drying temperatures. Concerning the physical properties, preference was obtained from the treatment of pumpkin and brown rice at a ratio of 50:50 at a temperature of 160°C. The chemical composition of the instant porridge included 5.62% water, 12.37% protein, 3.70% fat, 1.81% ash, 1.361.79 (mg GAE/g) phenolic, 164.36(µg/g) beta carotene and 41.5% RSA antioxidants.